2023
DOI: 10.3389/fendo.2023.1269672
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor VAX1 in VIP neurons of the suprachiasmatic nucleus impacts circadian rhythm generation, depressive-like behavior, and the reproductive axis in a sex-specific manner in mice

Brooke M. Van Loh,
Alexandra M. Yaw,
Joseph A. Breuer
et al.

Abstract: BackgroundThe suprachiasmatic nucleus (SCN) within the hypothalamus is a key brain structure required to relay light information to the body and synchronize cell and tissue level rhythms and hormone release. Specific subpopulations of SCN neurons, defined by their peptide expression, regulate defined SCN output. Here we focus on the vasoactive intestinal peptide (VIP) expressing neurons of the SCN. SCN VIP neurons are known to regulate circadian rhythms and reproductive function. MethodsTo specifically study S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 143 publications
0
2
0
Order By: Relevance
“…Therefore, VIP inputs from the SCN directly onto GnRH neurons, long ago identified (Beek et al, 1993), remain a candidate for gating kisspeptin responsiveness and onset of the LH surge. A recent study showing greater GnRH sensitivity to kisspeptin when VIP expression is abnormal, further supports this hypothesis (Van Loh et al, 2023).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Therefore, VIP inputs from the SCN directly onto GnRH neurons, long ago identified (Beek et al, 1993), remain a candidate for gating kisspeptin responsiveness and onset of the LH surge. A recent study showing greater GnRH sensitivity to kisspeptin when VIP expression is abnormal, further supports this hypothesis (Van Loh et al, 2023).…”
Section: Discussionmentioning
confidence: 64%
“…Functionally, GnRH neurons in females contacted by VIP preferentially expressed c-fos at the time of the GnRH/LH surge ( Beek et al, 1994 ) and infusion of VIP antisense in SCN impairs c-fos expression in these GnRH neurons ( Gerhold et al, 2005 ; Kahan et al, 2023 ). In addition, a recent study showed that the loss of the VAX1 transcription factor required for normal VIP expression, delays puberty onset, alters females estrous cycle length and potentiates the GnRH response to kisspeptin stimulation ( Van Loh et al, 2023 ). Together, the experimental evidence highlights the importance of VIP signaling, from cells in the SCN to GnRH neurons, for maintenance of normal reproductive function.…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, these coordinated oscillations are mediated by the SCN ( 23 ). The SCN is closely related to the secretion of gonadotropin-releasing hormone (GnRH) neurons and a variety of reproductive hormones ( 24 ). One pathway comprises direct innervation of GnRH neurons by the SCN ( 25 , 26 ), while the other involves an indirect circuitry where the SCN communicates with the HPG axis via Kisspeptin neurons ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…coordinated oscillations are mediated by the SCN (23). The SCN is closely related to the secretion of gonadotropin-releasing hormone (GnRH) neurons and a variety of reproductive hormones (24). One pathway comprises direct innervation of GnRH neurons by the SCN (25, 26), while the other involves an indirect circuitry where the SCN communicates with the HPG axis via Kisspeptin neurons (27,28).…”
Section: Discussionmentioning
confidence: 99%